Functionalizing Designer DNA Crystals with a Triple‐Helical Veneer1. (11th March 2014) - Rusling, David A.; Chandrasekaran, Arun Richard; Ohayon, Yoel P.; Brown, Tom; Fox, Keith R.; Sha, Ruojie; Mao, Chengde; Seeman, Nadrian C.
Abstract DNA is a very useful molecule for the programmed self‐assembly of 2D and 3D nanoscale objects.1 The design of these structures exploits Watson–Crick hybridization and strand exchange to stitch linear duplexes into finite assemblies.2–4 The dimensions of these complexes can be increased by over five orders of magnitude through self‐assembly of cohesive single‐stranded segments (sticky ends).5, 6 Methods that exploit the sequence addressability of DNA nanostructures will enable the programmable positioning of components in 2D and 3D space, offering applications such as the organization of nanoelectronics, 7 the direction of biological cascades, 8 and the structure determination of periodically positioned molecules by X‐ray diffraction.9 To this end we present a macroscopic 3D crystal based on the 3‐fold rotationally symmetric tensegrity triangle3, 6 that can be functionalized by a triplex‐forming oligonucleotide on each of its helical edges.